Creating Effective Post-Pandemic Psychiatric Nursing Clinical Experiences Using the Roy Adaptation Model. (December 2022) - Quidley-Rodriguez, Narciso; de Tantillo, Lila; Wolf, Lindsay J.
Introduction: The COVID-19 pandemic significantly impacted students in psychiatric clinical rotations. Clinicals were frequently limited or canceled, restricting exposure of student nurses to this experience. Many modifications led to permanent changes in the psychiatric clinical setting. Objectives: The purpose of this manuscript is to provide a cohesive approach to serving student nurses in the post-pandemic psychiatric clinical setting. Methods: A theoretical exploration of the literature framed by the Roy Adaptation Model (RAM) was conducted. Discussion: Results are presented using the four modes of the theory: Physiological, Self-Concept, Role Function, and Interdependence. Conclusions: Findings include strategies to enhance student learning while supporting students' health and wellness. Educators and practitioners should provide high-quality, safe learning environments for student nurses.